Mean-variance asset-liability management with inside information. Issue 7 (3rd April 2022) - Peng, Xingchun; Chen, Fenge
Abstract: This paper studies an asset-liability management (ALM) problem under mean-variance criterion with inside information. The asset-liability manager is allowed to invest in a financial market composed of a bond and a stock. The stock price process is governed by a diffusion process with random parameters. The uncontrolled liability process is described by a general diffusion process with hedgeable risks and unhedgeable risks. We model the inside information by a general random variable related to the future values of financial assets and liabilities. By using the Donsker Delta functional technique and the BSDE method, we derive the analytic expressions of efficient strategy and efficient frontier. To illustrate the general result, an example is provided in which the efficient strategy and efficient frontier are obtained in closed form. The comparison of efficient frontiers with and without inside information demonstrates that taking advantage of inside information can improve the efficient frontier.